2017
DOI: 10.1177/0266242617695382
|View full text |Cite
|
Sign up to set email alerts
|

The lack of short-term impact of cohesion policy on the competitiveness of SMEs

Abstract: The purpose of this article is to study the relationship between the competitiveness of small- and medium-sized companies and the public support offered to them in the form of direct subsidies allocated through European structural funds. Using micro-data gathered by the Operational Programme Enterprise and Innovations for Competitiveness (OPEIC) of European structural funds from 2007–2013, this analysis focuses on small- and medium-sized enterprises (SMEs) in the Czech Republic. We employed a counterfactual ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 42 publications
(51 reference statements)
4
19
0
Order By: Relevance
“…However, the effect is statistically insignificant. Although the positive sign of the coefficients indicates an increase in labour cost (as suggested by Čadil et al, ), it may be due to the creation of new employment opportunities), the value added per labour cost has also increased. This result can be assessed positively—despite the growth in labour costs, a statistically significant increase was proved in the value added per labour cost reflecting the productivity of labour costs.…”
Section: Resultsmentioning
confidence: 86%
See 3 more Smart Citations
“…However, the effect is statistically insignificant. Although the positive sign of the coefficients indicates an increase in labour cost (as suggested by Čadil et al, ), it may be due to the creation of new employment opportunities), the value added per labour cost has also increased. This result can be assessed positively—despite the growth in labour costs, a statistically significant increase was proved in the value added per labour cost reflecting the productivity of labour costs.…”
Section: Resultsmentioning
confidence: 86%
“…In our study, the supported companies manifested a statistically significant increase in value added per labour cost. Generally, the results in this context are inconsistent—while Špička et al (), Nilsson (), and Michalek () also found a positive impact of investment support on labour productivity, this has not been proven by Čadil et al ().…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…Most of the recent studies in the Central and Eastern European region have been focused on the evaluation of cohesion R&D policies and those aimed at the elimination of the regional disparities, e.g., [60][61][62][63][64][65][66][67][68][69][70], policies facilitating trainings and education [71,72] and effectivity of the self-employment programmes for the unemployed [73][74][75]. However, based on a search in the databases of previously published academic articles and research reports, no study has been focused on the evaluation of entrepreneurship support through the financial instruments yet.…”
Section: Introductionmentioning
confidence: 99%